2014
DOI: 10.15288/jsad.2014.75.486
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Readiness to Change: Alcohol Use and Help-Seeking Behavior

Abstract: ABSTRACT. Objective: Pre-post changes in readiness for change (RC) are commonly assessed in treatment outcome studies, often with contradictory results. Little is known about 12-month RC trajectories among those initiating change or about the association between RC and either within-or between-person alcohol use or time-lagged help-seeking behavior. Method: This observational longitudinal study measured RC as ambivalence, problem recognition, and taking steps. Participants (N = 253; 66.4% male) diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…This suggests that although RAH may potentiate benefits from brief interventions, its impact could be relatively short-lived. Recent data (Rice et al, 2014) support the finding that trajectories of readiness change over time among drinkers. Despite the complexity and diversity in these trajectories, these recent data also demonstrate that taking steps to change drinking increases days of abstinence and reduces drinking.…”
Section: Discussionmentioning
confidence: 66%
“…This suggests that although RAH may potentiate benefits from brief interventions, its impact could be relatively short-lived. Recent data (Rice et al, 2014) support the finding that trajectories of readiness change over time among drinkers. Despite the complexity and diversity in these trajectories, these recent data also demonstrate that taking steps to change drinking increases days of abstinence and reduces drinking.…”
Section: Discussionmentioning
confidence: 66%
“…Research has identified problem recognition and the perceived costs and benefits of reducing use as key elements of motivation for change and likelihood of taking steps toward reducing substance use (Rice, Hagler, & Tonigan, 2014; Walters, Lee, & Walker, 2012). Hence, the current study tested a model predicting these outcomes from the motivational context of marijuana use to determine how use motives and perceived utility of use in achieving goals are related to motivation for change.…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic construct is often the focus of behavioral intervention approaches which research has shown can be effective in reducing substance abuse behaviors (Smedslund et al 2011). Readiness to change is a focus of counseling approaches such as motivational interviewing (MI), and is assessed to determine if an individual is aware of their problem, is making plans to change their problem behavior, or has already engaged in change behaviors (Miller et al 1996; Rice, et al 2014). Readiness to change has been shown to affect how well an individual engages with the counselor and the therapy, and there is evidence of the indirect effect of pre-treatment readiness to change on treatment outcomes (Rice et al 2014).…”
Section: Introductionmentioning
confidence: 99%